Can barium support the release of acetylcholine by nerve impulses? - Silinsky, E M (1977)
Conventional electrophysiological techniques were used to study the effects of Ba on the release of acetylcholine (ACh) from frog motor nerve terminals. Equimolar substitution of Ba for Ca eliminated end-plate potentials (e.p.ps) without a corresponding decline in the amplitude of the nerve terminal action potential. Miniature end-plate potentials (m.e.p.ps) were readily detectable in Ba solutions despite a depolarized muscle membrane. Studies on the e.p.p. in curarized preparations bathed with different concentrations of Ca and Ba suggest that Ba may compete with Ca in the process by which depolarization of the nerve terminal leads to the release of ACh. Repetitive nerve stimulation at 1 Hz in Ba solutions caused 5-20 fold increases in m.e.p.p. frequencies (7 experiments). Stimulation of Ba-bathed preparations at 10 Hz elevated m.e.p.p. frequencies to very high levels that could not be measured accurately (''100/s). It is suggested that the asynchronous discharge of m.e.p.ps produced by repetitive nerve stimulation is the electrophysiological correlate of the evoked ACh outflow in Ba solutions detected previously by bioassay of ther perfusion fluid.